A parametric study of flutter behavior of a composite wind turbine blade with bend-twist coupling. (1st January 2019) - Shakya, Praveen; Sunny, Mohammed Rabius; Maiti, Dipak Kumar
Abstract: Now a days wind turbine blades are generally designed to have length as high as 60 m or more to maximize power production. Aeroelastic instabilities such as flutter are major concerns for these long, flexible and slender blades. Stiffness coupling between bending and twisting modes can be used to improve the aeroelastic performance of such blades. In composite blades bend twist coupling can be achieved by imparting unbalance in the lamination sequence. In the present work, a parametric study has been conducted to study the effect of unbalances in different parts of a wind turbine blade on flutter instability. An eigenvalue-based approach has been used for flutter analysis. It has been observed that flap-torsional stiffness has high impact on critical flutter speed. The critical flutter speed is increased by 40% with flap-torsional stiffness due to the unbalance in the entire section of the blade with symmetric skin, while for asymmetric skin; the achievable increment is 100%. The unbalance in the spar cap of the blade has less critical flutter speed as compared to the unbalance in the entire section of the blade. Unbalance in the entire section of the blade with asymmetric skin can lead to highest flutter speed.